All solution-processed red organic light-emitting diode based on a new thermally cross-linked heteroleptic Ir(iii) complex. Issue 43 (30th October 2018) - Cho, Woosum; Reddy, Saripally Sudhaker; Kim, Junyoung; Cho, Young-Rae; Jin, Sung-Ho
Abstract : A novel cross-linkable red iridium(iii ) complex and electron transport material were designed and synthesized. The newly cross-linkable red Ir(iii ) complex was successfully thermally cross-linked with a cross-linkable host in the emitting layer (EML). After cross-linking, the EML was not damaged by organic solvents. Abstract : A novel cross-linkable red iridium(iii ) complex and electron transport material were designed and synthesized for use in the fabrication of solution-processed phosphorescent organic light-emitting diodes (PHOLEDs). The newly cross-linkable red Ir(iii ) complex was successfully thermal cross-linked with a cross-linkable host in the emitting layer (EML). After cross-linking, the EML was found not to be damaged by organic solvents. A maximum external quantum efficiency (EQE) of 4.64% (2.77 cd A −1 ) was achieved for deep-red PHOLEDs after rinsing, which was similar to the EQE of 4.59% (2.52 cd A −1 ) after rinsing the deep-red PHOLEDs with thermal cross-linking.